2003
DOI: 10.1029/2002jd002633
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil dust aerosol in China and its transport and distribution during 2001 ACE‐Asia: 2. Model simulation and validation

Abstract: A size‐segregated soil dust emission and transport model, Northern Aerosol Regional Climate Model (NARCM), was used to simulate the production and transport of Asian soil dust during the Aerosol Characterization Experiment‐Asia (ACE‐Asia) period from March to May 2001. The model is driven by the NCEP reanalyzed meteorology and has all the atmospheric aerosol physical processes of soil dust: production, transport, growth, coagulation, and dry and wet deposition. A Chinese soil texture map that infers the soil g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
308
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(335 citation statements)
references
References 32 publications
23
308
1
3
Order By: Relevance
“…Combined with the variations in AOD, the main reason for high AOD but low Ångström exponent in spring is the long-distance transport of dust particles from the north and northwest of China Gong et al, 2003). Convective precipitation occurs frequently in summer with the majority of coarse particles eliminated by wet settlement.…”
Section: Variations In the Monthly And Seasonal åNgström Exponentmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with the variations in AOD, the main reason for high AOD but low Ångström exponent in spring is the long-distance transport of dust particles from the north and northwest of China Gong et al, 2003). Convective precipitation occurs frequently in summer with the majority of coarse particles eliminated by wet settlement.…”
Section: Variations In the Monthly And Seasonal åNgström Exponentmentioning
confidence: 99%
“…Large AOD values appeared in the winter and spring and ranged from 0.45 to 0.47, from 0.53 to 0.55, from 0.72 to 0.74 and from 1.07 to 1.13 for each wavelength, respectively. In spring, the Sichuan Basin region could be affected by dust storms from North China (Gong et al, 2003), which could contribute high AOD over the Basin. While in winter, the cold air has weak effect on the Sichuan Basin, aerosol particles from local pollution sources could not diffuse well.…”
Section: Monthly and Seasonal Variations Of Aodmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, some studies (Zhang et al 2003 have showed that the DS3 is the strongest one with the longest transportation from East Asia crossing Pacific Ocean to the west coast of America, which is called as ''perfect dust storm''. In this paper we mainly focused on this dust storm to evaluate the radiative forcing over East Asia and North Pacific region (75 E-225 W, 16-70 N) and examine the impacts of dust optical properties on it.…”
Section: Introductionmentioning
confidence: 99%
“…For the coarse-mode particles, N 1-10 was not only very high in the cold season but also remained at its highest number concentration in spring, which is characterized by local soil dust or dust events. Gong et al (2003) noted that ~252.8 Mt of soil dust was estimated to have been produced in the East Asian deserts in a spring season, with ~60% of this being due to four major dust storms. When dust storms occur over northern China, N 1-10 can increase sharply.…”
Section: Temporal Variability Of Aerosol Propertiesmentioning
confidence: 99%